Keanekaragaman Makroalga Pantai Batu Layar, Lombok Barat, Nusa Tenggara Barat - Ghazali, Mursal; Nurhayati, Nurhayati; Jupri, Ahmad; Murdiah, Murdiah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Macroalgae are photosynthetic organisms that grow in aquatic environments and play an important role in marine and coastal ecosystems. Macroalgae grow in almost all waters, including in the coastal area of Batu Layar. Batu Layar has particular and distinctive characteristics compared to other locations on Lombok Island. However, in recent years, supporting tourism facilities have begun to be built which will affect the composition of living biota including macroalgae. Therefore, data was collected on the diversity of changes in the composition of macroalgae in the future. This study aims to determine the diversity of macroalgae growing on Batu Layar Beach, West Lombok. This study is a descriptive exploratory study. Quadrant placement and sampling were carried out using the purposive sampling method. The results showed that the number of species growing in Batu Layar waters was 41 species. These species are spread across two observation stations. Station 1 is dominated by S. polycystum while station 2 is dominated by P. australis. The current strength and depth parameters of Station 1 were higher than those of Station 2, while the ammonia, phosphate and turbidity of Station 2 were higher than those of Station 1.